Biological Stress Reactivity and Introspective Sensitivity: An Exploratory Study - Barrientos, Mauricio; Tapia, Leonel; Silva, Jaime R.; Reyes, Gabriel (Frontiers in Psychology, 2020)
It is well established that reaction to stressful events is highly variable among individuals, with an impact on several cognitive processes, such as memory, attention and perception. However, whether individuals sensitivity to stress is related to their introspective performance is still unclear. Here we investigated whether biological reactivity to stress is related to how individuals evaluate their own cognitive processes (introspection). Through hormone measures (cortisol concentration in saliva), we quantified the intensity of the stress response in 27 healthy individuals. Then, using a visual search paradigm we investigated introspective capacity. On a trial-by-trial basis, we evaluated three introspective measures: confidence level, subjective response time (introspective response time; iRT) and the subjective estimation of attentional shifts (subjective number of scanned items; SNSI) during a perceptual decision task. Results suggest that biological reactivity to stress predicts lower sensitivity in introspection. In short, highly stress-reactive individuals are poor introspectors.